1987
DOI: 10.1177/35.2.3540104
|View full text |Cite
|
Sign up to set email alerts
|

Tartrate-resistant acid phosphatase in bone and cartilage following decalcification and cold-embedding in plastic.

Abstract: Tartrate-resistant acid phosphatase (TRAP) has been proposed as a cytochemical marker for osteoclasts. We have developed an improved technique for the localization of TRAP in rat and mouse bone and cartilage. This procedure employs JB-4 plastic as the embedding medium, permits decalcification, and results in improved morphology compared with frozen sections. Peritoneal lavage cells were used to determine the appropriate isomer and concentration of tartrate necessary for inhibition of tartrate-sensitive acid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
95
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(100 citation statements)
references
References 9 publications
2
95
0
3
Order By: Relevance
“…TRAP staining of the scales was performed by the methods of Cole and Walters [35]. After TRAP staining, the specimens were counterstained with 4', 6-diamino-2-phenylindole (DAPI) (Molecular Probes, Inc., Eugene, OR, USA).…”
Section: Effect Of Fugu Pth1(1-34) On the Differentiation Of Mononuclmentioning
confidence: 99%
“…TRAP staining of the scales was performed by the methods of Cole and Walters [35]. After TRAP staining, the specimens were counterstained with 4', 6-diamino-2-phenylindole (DAPI) (Molecular Probes, Inc., Eugene, OR, USA).…”
Section: Effect Of Fugu Pth1(1-34) On the Differentiation Of Mononuclmentioning
confidence: 99%
“…Subsequently, osteoclasts were observed by TRAP staining using the methods of Cole and Walters (1987). Osteoblasts were detected by alkaline phosphatase (ALP) staining using a kit (NBT/BCIP Stock Solution, Roche Applied Science, Mannheim, Germany).…”
Section: Morphological Study Of Osteoclasts and Osteoblasts In The Scmentioning
confidence: 99%
“…1 Clusters of tumor cells stained strongly positively for tartrate-resistant acid phosphatase, suggesting that the neoplastic cells were derived from mononuclear cells of the dental follicle, which stain similarly. 4 Studies have shown that mononuclear cells, probably derived from monocytes, 3,4,6 begin to accumulate in the dental follicle of developing teeth immediately prior to eruption. These cells are considered precursors for osteoclasts that appear soon thereafter and are responsible for the resorption of bony tissues and deciduous dental tissues seen during tooth eruption.…”
mentioning
confidence: 99%
“…The cells were positive for vimentin and negative for all other markers. Subsequently, the same blocks were stained histochemically fur tarn-ate-resistant acid phosphatase, a mark- follicular origin for the tumor cells is the expression of tartrate-resistant acid phosphatase, an enzymatic marker of mononuclear cells of the dental follicle 4 with the potential to differentiate into osteoclasts. 1 Multiple neoplasms developed simultaneously at several sites in the mandible and maxilla of this young dog.…”
mentioning
confidence: 99%